2018
DOI: 10.1177/0963689718798627
|View full text |Cite
|
Sign up to set email alerts
|

Omental Pouch Technique for Combined Site Islet Autotransplantation Following Total Pancreatectomy

Abstract: Total pancreatectomy and islet autotransplantation (TPIAT) is an effective treatment for selected patients with chronic pancreatitis. The portal circulation is the standard infusion site for islet transplant, but marked elevation of portal pressures may prevent complete islet infusion. Herein we report a novel technique of combined site islet autotransplantation using an omental pouch. This technique may be useful when technical limitations prevent complete intraportal transplantation. In four TPIAT recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Insulin independence necessitates adequate islet engraftment without fibrosis, which is currently only offered with omentum and intraportal ICT. Omental ICT has demonstrated positive early results in animal and human studies [ 125 , 128 , 129 ]. Stice et al (2018) demonstrated successful omental autologous ICT in four patients confirming prior promising animal studies.…”
Section: The Promise and Future Challenges For Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin independence necessitates adequate islet engraftment without fibrosis, which is currently only offered with omentum and intraportal ICT. Omental ICT has demonstrated positive early results in animal and human studies [ 125 , 128 , 129 ]. Stice et al (2018) demonstrated successful omental autologous ICT in four patients confirming prior promising animal studies.…”
Section: The Promise and Future Challenges For Stem Cellsmentioning
confidence: 99%
“…Stice et al (2018) demonstrated successful omental autologous ICT in four patients confirming prior promising animal studies. The omentum releases hormones into portal circulation, supports islet engraftment, and is relatively accessible if resection is needed [ 128 , 129 ]. The omentum also limits IBMIR, since no direct blood contact occurs [ 129 ].…”
Section: The Promise and Future Challenges For Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The omentum appears to provide more rapid revascularization compared with intrahepatic islets 36 . In humans, patients receiving autologous IT due to chronic pancreatitis have partially been transplanted to the omental pouch, in cases when increased portal pressure prevented complete intraportal transplantation 40 . However, results are so far disappointing, with only a small number of patients that have been rendered insulin independent, while the majority of grafts have failed.…”
Section: Alternative Implantation Sites and Comparative Studiesmentioning
confidence: 99%
“…Baidal et al reported an allotransplant to the omentum in a type 1 diabetic recipient who achieved insulin independence at one year follow up [85]. At the University of Minnesota, islets are occasionally placed into the omentum or peritoneum when prohibitive portal pressures prevent the full volume of islets from being transfused during TPIAT [86]. There is a clinical trial ongoing where a portion of islets are placed in the omentum regardless of portal pressures (NCT03779139).…”
Section: Omentummentioning
confidence: 99%